Effect of a step-training program on muscle strength in older women - Daniela Coelho Zazá; Hans-Joachim Karl Menzel; Mauro Heleno Chagas (Universidade Federal de Santa Catarina, 2010)
Step-training is associated with strength improvement of the lower limbs. Muscle strength is a critical component for the maintenance of functional capacity. The objective of the present study was to determine the effect of 6 weeks of step-training on work and power of the lower limbs in older women. Thirteen healthy and active women volunteered to participate in the study. All subjects underwent step-training classes three times per week for 60 min. Strength variables of the knee extensor and flexor muscles were measured with a Biodex System 3 Pro isokinetic dynamometer. Muscle work and power were assessed at an angular velocity of 60 and 180°/s. A significant difference (p<0.05) in knee flexor muscle work was observed between pre- and post-test at 60 and 180°/s. There was a significant difference (p<0.05) in knee extensor muscle work between pre- and post-test at 60°/s. Significant differences were observed between pre- and post-test values of knee flexor muscle power at 60°/s (p<0.05) and knee extensor muscle power at 60 and 180°/s (p<0.05). In conclusion, step-training can be recommended as an alternative physical activity to increase strength performance (work and power) of the knee extensor and flexor muscles in older subjects.